Hubungan Teori Hukum Dengan Praktik Penegakan Hukum Di Indonesia - Holil, Moh (Prodi HKI IAI Miftahul Ulum Pamekasan, 2022)
Indonesia is a state of law, all state apparatus must act in accordance with the law and all people who live within the scope of Indonesia must obey the law. However, the applicable law in Indonesia has not yet shown its effectiveness, so that the purpose of the law has not been properly achieved. The term that is very familiar is